Tillage methods for the cropping of sorghum in legume fodder banks in the subhumid zone of Nigeria - Mohamed-Saleem, M.A.; Suleiman, H.; Kaufmann, Ralph R. von (Elsevier, 1987)
Studies different methods of growing sorghum in stylo fodder banks at ILCA, Kaduna. Includes ridging vs flat seedbed preparation, transplanting vs seeding, and suppressing or encouraging growth of forage legume during food crop growth.